2020
DOI: 10.1186/s43058-020-00078-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the CYP-IAPT transformation of child and adolescent mental health services in Cambridgeshire, UK: a qualitative implementation study

Abstract: Background The Children and Young People’s Improving Access to Psychological Therapies (CYP-IAPT) programme was introduced to transform Child and Adolescent Mental Health Services (CAMHS) across England. The programme comprised a set of principles that local CAMHS partnerships were expected to operationalise and embed with the aim of increasing access to services and improving the quality of care. This study explored how the implementation of the CYP-IAPT programme was executed and experienced by CAMHS profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These are changes that have preceded the current CAMHS transformation, and have focused on ensuring that there are both more CAMHS practitioners and that these practitioners are trained to deliver evidence-based psychological therapies to child and adolescent populations [48]. The studies reporting on these changes do share similar findings on operational difficulties, the need for stakeholder involvement and the importance of leadership, although actual service-related measures, such as in this study, have not been reported [49,50]. The current CAMHS transformation has been described in some publications [51] with qualitative work conducted on key stakeholders [52], although some concerns raised that insufficient young people and parents have been included [53].…”
Section: Plos Onementioning
confidence: 71%
“…These are changes that have preceded the current CAMHS transformation, and have focused on ensuring that there are both more CAMHS practitioners and that these practitioners are trained to deliver evidence-based psychological therapies to child and adolescent populations [48]. The studies reporting on these changes do share similar findings on operational difficulties, the need for stakeholder involvement and the importance of leadership, although actual service-related measures, such as in this study, have not been reported [49,50]. The current CAMHS transformation has been described in some publications [51] with qualitative work conducted on key stakeholders [52], although some concerns raised that insufficient young people and parents have been included [53].…”
Section: Plos Onementioning
confidence: 71%
“…educational psychologists in the TaMHS programme); and having a clear and agreed vision about programme scope and purpose, and how this related to existing provision and pathways. 25,26,31 Across programmes, implementation was further facilitated where relationships between partnering organisations were already established; for example, where individuals from local NHS services and education settings were already familiar with each other's roles, scope and expertise. 28,30,[32][33][34] Implementation was shaped not only by the quality, but also the constitution, of partnership working.…”
Section: Engagement and Cross-organisational Workingmentioning
confidence: 99%
“…funding cuts) in the wider environment. 26,27,31 Another central challenge reported for all three programmes was a lack of common understanding and language for mental health, which acted as a barrier to partnership working between sectors (e.g. between health and education) and within them (e.g.…”
Section: Engagement and Cross-organisational Workingmentioning
confidence: 99%
See 1 more Smart Citation
“…Local service providers continue facing barriers to communication due to diverse organisational cultures, restraining the development of a joined-up care system (Care Quality Commission, 2018). Finally, efforts of embedding EBPs and ROMs in practice have encountered challenges due to limited implementation guidance (Burn et al , 2020).…”
Section: Introductionmentioning
confidence: 99%